2024
DOI: 10.1177/02683555241227017
|View full text |Cite
|
Sign up to set email alerts
|

Third generation of laser (>1900) for endovenous thermoablation (EVLA) of varicose veins: A systematic review and meta-analysis

Luca Palombi,
Monica Morelli,
Dario Bruzzese
et al.

Abstract: Objectives Third generation lasers with longer wavelengths (>1900 nm) have been introduced, in recent years, for the treatment of varicose veins. The possible advantage of the new generation lasers is that they allow complete damage to the vein wall using a lower Power in Watts (W: J/sec) and a lower linear energy density (LEED: J/cm). The aim of this work is to evaluate the results present in the literature regarding efficacy and safeness of the new generation lasers for the treatment of varicose veins. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The studies currently present in the literature regarding the third-generation lasers (>1900 nm) report clinical results superimposable to those of the second generation, in terms of occlusion rate, but with a significant reduction in LEED values. In our recent review of the literature we have found a pooled mean estimates value of LEED equal to 38.2 J/cm with a very large heterogeneity (31 -59 J/cm) [21]. In reviewing the data, a high overall occlusion rate of 99.8% was found.…”
Section: Energymentioning
confidence: 84%
“…The studies currently present in the literature regarding the third-generation lasers (>1900 nm) report clinical results superimposable to those of the second generation, in terms of occlusion rate, but with a significant reduction in LEED values. In our recent review of the literature we have found a pooled mean estimates value of LEED equal to 38.2 J/cm with a very large heterogeneity (31 -59 J/cm) [21]. In reviewing the data, a high overall occlusion rate of 99.8% was found.…”
Section: Energymentioning
confidence: 84%